Skeletal muscle proteasome can degrade proteins in an ATP-dependent process that does not require ubiquitin. - Driscoll, J (1989)
The proteasome (the multicatalytic endoproteinase complex) in mammalian tissues hydrolyzes proteins and several types of peptides. When this structure was isolated rapidly from rabbit skeletal muscle in the presence of glycerol, its various peptidase and protease activities showed a large reversible activation by physiological concentrations of ATP (Ka = 0.3-0.5 mM). Hydrolysis of succinyl-Leu-Leu-Val-Tyr-(4-methylcoumaryl-7-amide) was stimulated up to 12-fold by ATP, whereas degradation of casein and bovine serum albumin increased 4- to 7-fold. Neither ADP nor AMP had any effect. CTP, GTP, UTP, and the nonhydrolyzable analogs adenosine 5'-[beta,gamma-imino]triphosphate (AMPP[NH]P) and adenosine 5'-[alpha,beta-methylene]triphosphate (AMP[CH2]PP) increased peptide hydrolysis as well as ATP did. However, only ATP stimulated casein breakdown and only in the presence of Mg2+. Thus, nucleotide binding allows activation of the peptidase functions, but ATP hydrolysis seems necessary for enhanced degradation of proteins. The ATP effect on proteolysis was reversible and did not require ubiquitin. Sensitivity to ATP was labile, and with storage at 4 degrees C the enzyme became fully active in the absence of ATP or Mg2+. The ATP-activated form closely resembles the proteasome complex described previously, which did not show ATP dependence: both have molecular masses of 650 kDa, contain the same 8-10 subunits, and are precipitated by the same antibodies. A similar ATP-activated form was found in rabbit liver but not in rabbit reticulocytes. The proteasome seems to represent a ubiquitin-independent, ATP-stimulated proteolytic activity within nucleated mammalian cells.